Faktor-Faktor Yang Mempengaruhi Peningkatan Kualitas Mutu Instansi Pendidikan Dan Pembelajaran - Arnita Niroha Halawa; Dety Mulyanti (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
Improving the quality of education for an educational institution is currently a top priority. This is the most important part in building sustainable education, therefore educators/educational staff must have a management principle in carrying out the level of change or development towards quality education. The purpose of writing this scientific article is to find out and review from a theoretical point of view and conduct discussions with previous theories. The method used is a theoretical review by analyzing and comparing existing theories. The result of this theoretical review is that the factors that affect the improvement of the quality of education quality are influenced by internal and external factors and in terms of resources. It can be concluded that the factors that influence the quality of education in educational institutions are an integral part that cannot be separated. These factors support the improvement of higher quality education and become indicators or standards of education and teaching. For educational institutions, it is necessary to develop teaching materials, develop learning strategies and methods, develop learning media, assessment, evaluation and assessment systems as well as educational curricula to improve the quality of teaching quality. It is also necessary for educational institutions to conduct monitoring and evaluation in as well as a more modern development program.